Lubrication Performance of Gas-Lubricated Inclined Slider Bearing with Micro-Grooves - Fuxi Liu; Wu Guo; Yang Li; Chunjie Yang; Hongbo Kang; Zhangyu Chen; Guansheng Wu; Binhui Han; Chaofeng Zhao; Xiang Liu (Journal of Applied Science and Engineering, 2024)
The aim of this paper is to investigate the effect of micro grooves on the lubrication performance of gas-lubricated inclined slider bearing. This paper is based on numerical analysis. The detailed numerical investigation is carried out in matlab software. The grooving parameters are optimized to obtain the maximum average pressure for various inclination angles of gas-lubricated inclined slider bearing. The results show that the inclination angle of the micro-grooves, depth of the micro-grooves, width of the micro-grooves, and spacing of the micro-grooves have an important influence on the hydrodynamic pressure of gas-lubricated inclined slider bearing with micro-grooves. Besides, the influence of the sliding speed on average pressure increment for various inclination angles of gas-lubricated inclined slider bearing is investigated. It is observed that the sliding speed generating the maximum average pressure increment is dependent on the inclination angle of gas-lubricated inclined slider bearing.